Curatorial Practices for Intersectional Programming - Hagan, Cara (The International Journal of Screendance, 2018)
Screendance finds its roots in the traditions of concert dance, museum culture, and film festivals. Film festivals - from which we borrow the structure for programming screendance - boast a history of discrimination towards bodies of color, varied gender expressions, bodies of different abilities, and more. Through an exploration of the history and socio-cultural context of film festivals in the west and dialogue with curators and directors from a handful of screendance festivals across the United States, this piece will present a set of curatorial challenges particular to our field, the creative solutions being explored by presenters and champions of screendance, and a consideration of where the field falls short, so we can better mitigate issues of underrepresentation of marginalized groups in screendance spaces.